BVES‐AS1 inhibits the malignant behaviors of colon adenocarcinoma cells via regulating BVES. (3rd June 2021) - Wen, Wu; Wang, Haiyan; Xie, Shuang; Wu, Zuyin; Zhang, Chunxu
Abstract: The underexpression of the long noncoding RNA blood vessel epicardial substance antisense RNA 1 (BVES‐AS1) has been shown in colon adenocarcinoma (COAD) patients. However, its role in COAD remains to be explored. This study aimed to investigate the function and potential mechanism of BVES‐AS1 in COAD. Colony formation, Cell Counting Kit‐8, JC‐1 mitochondrial membrane potential assay, wound healing, transwell, and western blot analyses were used to measure cell proliferation, apoptosis, migration, invasion, and epithelial‐mesenchymal transition (EMT) in COAD cells. RNA pull‐down, luciferase reporter, and RNA binding protein immunoprecipitation assays were used to detect the interaction of BVES‐AS1 and downstream genes. BVES‐AS1 was expressed at low levels in COAD cells. Overexpressed BVES‐AS1 inhibited COAD cell proliferation, migration, invasion, and EMT while elevating cell apoptosis. Mechanistically, BVES‐AS1 functioned as a competing endogenous RNA sponging miR‐522‐3p to regulate the expression of nearby gene blood vessel epicardial substance (BVES). Besides this, BVES‐AS1 recruited TATA‐box binding protein associated factor 15 (TAF15) to promote BVES messenger RNA stability. Taken together, our study confirmed that BVES‐AS1 inhibited COAD progression via interacting with miR‐522‐3p and TAF15 to regulate BVES expression, which might offer a perspective for COAD treatment.